COVID-19 Prevention and Control: Mining Industry Responses to the Pandemic - Susanto, Arif; Khaliwa, Agra Mohamad; Iqbal, Muhamad Razif; Putro, Edi Karyono; Abdilah, Asep Dian (UI Scholars Hub, 2022)
The rapidly growing global Coronavirus Disease 2019 (COVID-19) pandemic crisis affects the labor-intensive mining industry. The industry is characterized by high worker mobility and 24-hour operations; thus, this continuous, mobile workforce increases the transmission risk of COVID-19 and has been a challenge for the mining industry during the pandemic. PT X, one of the largest mineral mining locations in Mimika District, Central Papua Province, Indonesia, was challenged to face the COVID-19 pandemic crisis. Therefore, this qualitative study aimed to analyze the COVID-19 handling efforts by PT X Concentrating Division using a descriptive-analytical method to describe the completion of PT X. The assessment aimed to examine nine critical factors formulated by the International Labour Organization and evaluated as practical steps to prevent and mitigate the virus spread in the division. Furthermore, an analysis was conducted on data related to COVID-19 handling. The results showed that the nine critical factors had an average value of 89.41%. These results indicated that the pandemic handling efforts in the division had been implemented well.